MRI Lesion Load of Cerebral Small Vessel Disease and Cognitive Impairment in Patients With CADASIL - Shi, YuZhi; Li, ShaoWu; Li, Wei; Zhang, Chen; Guo, LiYing; Pan, YunZhu; Zhou, XueMei; Wang, XinGao; Niu, Songtao; Yu, XueYing; Tang, HeFei; Chen, Bin; et al. (Frontiers in Neurology, 2018)
Background and objective: Cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is the most common and best known monogenic small vessel disease (SVD). Cognitive impairment is an inevitable feature of CADASIL. Total SVD score and global cortical atrophy (GCA) scale were found to be good predictors of poor cognitive performance in community-dwelling adults. We aimed to estimate the predictive power of the total SVD score and GCA scale on the cognitive performance in patients with CADASIL. Methods: We enrolled 20 genetically confirmed CADASIL patients and 20 controls matched by age, gender and years of education. Participants underwent a series of assessments that included ratings of global cognition and specific tests of executive function, information processing speed, memory, language and visuospatial function. The total SVD score and GCA scale were rated. Results: The CADASIL group performed worse than the controls on all cognition measures. Neither global cognition nor any separate domain of cognition was significantly different among patients grouped by total SVD score. Negative correlations between the GCA score and cognitive performance were observed. Approximately 40% of the variance was explained by the total GCA score in the domains of executive function, information processing speed and language. The superficial atrophy score was associated with poor performance in most of the domains of cognition. Adding the superficial atrophy score decreased the prediction power of the deep atrophy score on cognitive impairment alone. Conclusions: The GCA score, not the total SVD score, was significantly associated with poor cognitive performance in patients with CADASIL. Adding the superficial atrophy score attenuated the prediction power of the deep atrophy score on cognitive impairment alone.